Imaging of pleural disease. - Qureshi, N; Gleeson, F (2006)
Imaging plays an important role in the diagnosis and subsequent management of patients with pleural disease. The presence of a pleural abnormality is usually suggested following a routine chest x-ray, with a number of imaging modalities available for further characterization. This article describes the radiographic and cross-sectional appearances of pleural diseases, which are commonly encountered in every day practice. The conditions covered include benign and malignant pleural thickening, pleural effusions, empyema and pneumothoraces. The relative merits of CT, MRI and PET in the assessment of these conditions and the role of image-guided intervention are discussed.